2017
DOI: 10.1128/jvi.00064-17
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Interaction of Lentiviral Vif Molecules with HIV-1 Gag and Differential Effects of Species-Specific Vif on Virus Production

Abstract: The virion infectivity factor (Vif) open reading frame is conserved among most lentiviruses. Vif molecules contribute to viral replication by inactivating host antiviral factors, the APOBEC3 cytidine deaminases. However, various species of lentiviral Vif proteins have evolved different strategies for overcoming host APOBEC3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
2
0
1
Order By: Relevance
“…The DSB is repaired by nonhomologous end-joining (NHEJ) associated with InDel mutations at the cut site. tat, rev, vif, vpr, vpu, nef (Cavrois et al, 2017;Jakobsdottir et al, 2017;Joseph et al, 2014;Zheng et al, 2017) SIV NHP LYM, Mo, Mϕ, DC, MG 1° Receptor: CD4 Co-receptors: CCR5 or CXCR4 tat, rev, vif, vpr, vpu, vpx, nef (Merino et al, 2017;Micci et al, 2014;Sugimoto et al, 2017) FIV F, (NHP) LYM, Mo, MΦ, MG, Astro 1° Receptor: CD134 Co-receptor: CXCR4 rev, vif (Eckstrand et al, 2017;Meeker and Hudson, 2017;Meeker et al, 2012;Meltzer et al, 1990;Power, 2018) BIV B LYM, Mo, MΦ, FBLC, N, MG, BMEC CXCR5 suspected tat, rev, vif, vpw, vpy, tmx (Bhatia et al, 2013;Guo et al, 2013;Zhang et al, 1997Zhang et al, , 2014 SRLV (CAEV and MVV) O, C Mo, MΦ, DC, MG, BMEC, LYM, EC of MaGd Not yet identified; mannose receptor suspected rev, v...…”
Section: Discussionmentioning
confidence: 99%
“…The DSB is repaired by nonhomologous end-joining (NHEJ) associated with InDel mutations at the cut site. tat, rev, vif, vpr, vpu, nef (Cavrois et al, 2017;Jakobsdottir et al, 2017;Joseph et al, 2014;Zheng et al, 2017) SIV NHP LYM, Mo, Mϕ, DC, MG 1° Receptor: CD4 Co-receptors: CCR5 or CXCR4 tat, rev, vif, vpr, vpu, vpx, nef (Merino et al, 2017;Micci et al, 2014;Sugimoto et al, 2017) FIV F, (NHP) LYM, Mo, MΦ, MG, Astro 1° Receptor: CD134 Co-receptor: CXCR4 rev, vif (Eckstrand et al, 2017;Meeker and Hudson, 2017;Meeker et al, 2012;Meltzer et al, 1990;Power, 2018) BIV B LYM, Mo, MΦ, FBLC, N, MG, BMEC CXCR5 suspected tat, rev, vif, vpw, vpy, tmx (Bhatia et al, 2013;Guo et al, 2013;Zhang et al, 1997Zhang et al, , 2014 SRLV (CAEV and MVV) O, C Mo, MΦ, DC, MG, BMEC, LYM, EC of MaGd Not yet identified; mannose receptor suspected rev, v...…”
Section: Discussionmentioning
confidence: 99%
“…Відкрита рамка зчитування фактору інфекційності віріону Vif (virion infectivity factor) є консервативною для більшості лентівірусів. Молекули Vif приймають участь у реплікації вірусу за допомогою інактивування антивірусних факторів хазяїна, зокрема, цитидин деамінази APOBEC3 [22].…”
Section: структурний аналіз протеїнів відкритих рамок зчитування віру...unclassified
“…To successfully replicate in host cells, viruses need to counteract various host restriction factors at different replication steps. It is evident from several reports that host restriction factors, such as apolipoprotein B mRNA-editing enzyme catalytic subunit 3 proteins (APOBEC3) [ 3 , 4 , 5 ], tripartite motif protein 5a (TRIM5a) [ 6 ], SAM domain and HD domain-containing protein 1 (SAMHD1) [ 7 , 8 ], and tetherin [ 9 ] play important roles in blocking interspecies transmission of retroviruses. As with several other restriction factors, like interferon-induced transmembrane proteins (IFITMs), tetherin has been shown to have broad antiviral activity against different enveloped viruses from various virus families including human immunodeficiency virus 1 (HIV-1), Ebola virus and human herpes virus 8 (HHV8) [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%